“Speaking eloquently: right here and now” at the 2nd Infantry Division Headquarters, Tun Razak Camp in Bayan Lepas, Penang / Marni Jamil - Jamil, Marni (Academy of Language Studies, 2022)
In conjunction with Hari Pengajian Pegawai, Ms Marni Jamil, a lecturer from the Academy of Language Studies, UiTM Penang Branch was officially invited by the 2nd Infantry Division Headquarters, Tun Razak Camp in Bayan Lepas, Penang to conduct an interactive session on English communication skills at Wisma Pertiwi on 27 July 2022, from 8 p.m. to 10 p.m. The 2-hour session titled “Speaking Eloquently: Right Here And Now” was also graced by the presence of special guests, including Major General Dato' Haji Muhammad Huzaimi Sabri, the Commander of the 2nd Division of the Malaysian Infantry (2 Div), Colonel Mohd Tarmizi Haji Basri, the Division Artillery Commander (2 Div), Colonel Samad Igom, the Chief of Staff (2 Div) and Lieutenant Colonel Mat Zakila Muhamed, the President of the Officers' Mess Council (2 Div).